2020
DOI: 10.1038/s41388-020-01458-x
|View full text |Cite
|
Sign up to set email alerts
|

FGF18–FGFR2 signaling triggers the activation of c-Jun–YAP1 axis to promote carcinogenesis in a subgroup of gastric cancer patients and indicates translational potential

Abstract: Fibroblast growth factor receptor type 2 (FGFR2) has emerged as a key oncogenic factor that regulates gastric cancer (GC) progression, but the underlying mechanism of FGF–FGFR2 signaling pathway remains largely unknown. To identify the potential molecular mechanisms of the oncogenic FGFR2 in gastric carcinogenesis and convey a novel therapeutic strategy, we profiled the FGFR alterations and analyzed their clinical associations in TCGA and Hong Kong GC cohorts. We found that FGFR2 overexpression in GC cell line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 48 publications
1
25
0
Order By: Relevance
“…26 YAP1, a crucial transcriptional coactivator in the Hippo signaling pathway, is involved in the initiation and development of several cancers, including GC. 27,28 In 2004, Professor Lian confirmed that the RUNX2-YAP complex is essential for bone homeostasis, osteoblast activity, and mesenchymal stem cell (MSC) fate determination. 29,30 YAP1 can cooperate with RUNX2 and is crucial for the anchorage-independent growth of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…26 YAP1, a crucial transcriptional coactivator in the Hippo signaling pathway, is involved in the initiation and development of several cancers, including GC. 27,28 In 2004, Professor Lian confirmed that the RUNX2-YAP complex is essential for bone homeostasis, osteoblast activity, and mesenchymal stem cell (MSC) fate determination. 29,30 YAP1 can cooperate with RUNX2 and is crucial for the anchorage-independent growth of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Several signaling pathways have been found to participate in gastric tumorigenesis. For example, FGF18-FGFR2 signaling induces the c-Jun-YAP1 axis and enhances gastric carcinogenesis [ 27 ]. The role of Notch-1 in gastric cancer has been characterized in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…YAP1 is a downstream transcription coactivator of the Hippo signaling pathway, which acts not only as a prominent molecule for tumorigenesis, but also as an oncogenic driver in GC. 109 113 YAP1 plays a crucial role in CSC expansion and properties in various tumor types, including GC. 107 , 114 , 115 In fact, genetic knockdown of YAP1 has been found to suppress gastric CSC traits, tumorigenesis, and peritoneal metastasis in vitro and in vivo .…”
Section: Clinicopathological and Molecular Features Of Diffuse-type G...mentioning
confidence: 99%